2019
DOI: 10.1002/jsfa.9721
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nitrogen supply enhances the cellular antioxidant potential of phenolic extracts through alteration of the phenolic composition in lettuce (Lactuca sativa L.)

Abstract: BACKGROUND Nitrogen availability is an important environmental factor that determines the production of phenolic compounds in vegetables, but the relationship between low nitrogen‐induced alterations of phenolic compounds in vegetable crops and the cellular antioxidant activities of these compounds remains unclear. This study investigated the effect of reduced nitrogen supply (0.05 mmol L−1 nitrate) on phenolic metabolism in lettuce and the protective role of phenolic extracts against H2O2‐induced oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Consumers have become increasingly aware of the role of plantderived antioxidants, especially phenolic compounds, in reducing the risk of cancer, cardiovascular disease and accelerated aging. 5,7,15,26 Therefore, in recent years, many studies have been conducted with the aim of increasing phenolic accumulation in plants. Reducing the application of nitrogen during crop production can effectively improve the phenolic content in plants, although the mechanisms involved in this process remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consumers have become increasingly aware of the role of plantderived antioxidants, especially phenolic compounds, in reducing the risk of cancer, cardiovascular disease and accelerated aging. 5,7,15,26 Therefore, in recent years, many studies have been conducted with the aim of increasing phenolic accumulation in plants. Reducing the application of nitrogen during crop production can effectively improve the phenolic content in plants, although the mechanisms involved in this process remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase was 1% formic acid (solvent A) and 100% methanol (solvent B) with a flow rate of 0.7 mL min −1 . The gradient used was as follows: 0- 15 Quantitative and real-time PCR analysis Total RNA was extracted using the plant RNA purification kit. Firststrand cDNA was synthesized using HiScript II Q RT SuperMix in a 10 μL reaction volume containing 500 ng of purified RNA.…”
Section: Quantification Of Phenolic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrogen availability is an extremely important factor affecting the production of phenolic compounds in plants, with a reduction in nitrogen availability generally increasing their levels [12,13]. Our previous studies also found that proper nitrogen limitation could lead to increased accumulation of phenolic compounds in lettuce [14,15]. From an environmental standpoint, such a reduction promotes optimal efficiency in the use of nitrogen by plants, thereby limiting its loss in the environment.…”
Section: Introductionmentioning
confidence: 99%